Sue Blundell, Women in Ancient Greece, Translation by María Antonia de Miquel Serra, Barcelona, RBA Libros, 2025, 384 pages, ISBN 978-84-1098-146-1. (Minerva, 2025)
Review: Sue Blundell, Las mujeres de la antigua Grecia, traducción de María Antonia De Miquel Serra Barcelona, RBA Libros, 2025, 384 páginas, ISBN 978-84-1098-146-1